2011
DOI: 10.19030/jabr.v27i3.4218
|View full text |Cite
|
Sign up to set email alerts
|

Partnerships, Suppliers And Coercive Influence

Abstract: <span>This paper adapts intra-firm influence strategies to an inter-firm context. In the process it retests the link between coercive influence strategies and supplier performance. Qualitative data is drawn from interviews conducted with 17 informants in the Australian Recruitment Industry. In line with expectations, the study shows that intra-firm influence strategies are adaptable to an inter-firm context. Contrary to predictions, the study finds that suppliers use frequent checking and persistent remi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…These include: legitimating, rational persuasion, inspirational appeal, consultation, exchange, personal appeal, ingratiation, pressure, and coalition. As there are many similarities between the intrafirm and interfirm tactics, researchers have found that intrafirm influence tactics are adaptable for interfirm usage (Bignoux & Gray, 2011;Boyle, Dwyer, Robicheaux, & Simpson, 1992). Thus, in this paper I use the intrafirm labels for both intra and interfirm contexts.…”
Section: Definition and Features Of Influence Tacticsmentioning
confidence: 99%
“…These include: legitimating, rational persuasion, inspirational appeal, consultation, exchange, personal appeal, ingratiation, pressure, and coalition. As there are many similarities between the intrafirm and interfirm tactics, researchers have found that intrafirm influence tactics are adaptable for interfirm usage (Bignoux & Gray, 2011;Boyle, Dwyer, Robicheaux, & Simpson, 1992). Thus, in this paper I use the intrafirm labels for both intra and interfirm contexts.…”
Section: Definition and Features Of Influence Tacticsmentioning
confidence: 99%